STORYTELLING WITH FINGER PUPPET MEDIA: A SERVICE LEARNING ACTIVITY AT MIS TUNAS ISLAM, BOGOR DISTRICT - Hasanah, Tita; Humairoh, Aninda Nishfi; Iswandi, Delia; Puspita, Mutiara; Fitriyani, Sagita; Maesaroh, Siti Patimah; A’yuni, Siti Qurrota; Hasanah, Siti Zulfah (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2024)
This Community Service Activity (PKM) aims to implement one of the media created by students from Seni Budaya Keterampilan (the Art and Culture Skills) course, namely finger puppets through storytelling activities. The method used is service learning. The activities were carried out at MIS Tunas Islam, Pamijahan District, Bogor Regency. The target of this service activity is first grade students. The activity stages consist of planning, implementation and evaluation. In general, this PKM activities ran well and smoothly and provided several recommendations for further activities.